Electrooxidation and determination of dopamine using a Nafion (R)-cobalt hexacyanoferrate film modified electrode - Castro, Suely S. L. (2008)
The electrocatalysis of dopamine has been studied using a cobalt hexacyanoferrate film (CoHCFe)-modified glassy carbon electrode. Using a rotating disk CoHCFe-modified electrode, the reaction rate constant for dopamine was found to be 3.5 x 105 cm(3) mol(-1) s(-1) at a concentration of 5.0 x 10(-5) mol L-1. When a Nafion (R) film is applied to the CoHCFe-modified electrode surface a high selectivity for the determination of dopamine over ascorbic acid was obtained. The analytical curve for dopamine presented linear dependence over the concentration range from 1.2 x 10(-5) to 5.0 x 10(-4) mol L-1 with a slope of 23.5 mA mol(-1) L and a linear correlation coefficient of 0.999. The detection limit of this method was 8.9 x 10(-6) mol L-1 and the relative standard deviation for five measurements of 2.5 x 10(-4) mol L-1 dopamine was 0.58%.